Metaphorical Expression in Song Lyrics in English Textbook Senior High School - Catri Novita F. Manalu; Mila Kristi Sitopu; Ayu Paulina Silaban; Erikson Saragih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the metaphorical song lyrics in English textbooks in senior high school. This research is descriptive qualitative. This research's object is the Metaphor found in song lyrics in English textbooks in senior high school. Sources of data in this study are song lyrics found in English textbooks in senior high school. The songs included in the English textbooks are: 1. The world is ours by Alloe Black and David Correy; 2. Heal The World by Michael Jackson; 3. Breakaway by Kelly Clarkson; 4. Shake It Off by Taylor Swift. The method used by researchers is documentation in collecting data and analyzing data. In analyzing the data, the researcher used a Metaphor based on Lakoff and Johnson's theory, namely structural metaphors, orientation metaphors, and ontological metaphors. These are: containers and personifications. The results showed six structural Metaphors, five orientation metaphors, one container metaphor and two personification metaphors. Keywords: English Books, Metaphor, Song Lyric